A Systematic Review of Code Switching in Bilingual Education: Patterns, Trends, and Insight from English Classroom Practice - Syifana Arumaisya (Universitas Islam Negeri Palopo, 2025)
This study investigates the role of code-switching in bilingual educational settings, emphasizing its significance in enhancing students' comprehension and adaptability within diverse contexts. Despite its importance, the study identifies a notable gap in existing literature regarding the specific types of code-switching employed by teachers and students in classrooms. A systematic review was conducted to examine trends and research gaps in code-switching studies from 2013 to 2023, with an emphasis on peer-reviewed articles containing relevant keywords. The review used the Web of Science database and Boolean operators to reduce search results, yielding 579 articles. Following a thorough review, 25 studies were chosen for analysis, with a prevalence of mixed-methods and qualitative research methodologies. The findings demonstrated significant variances in methods of research over the last decade, with a shift in focus in bilingual education between 2018 and 2020. The study divides code-switching into three types: situational metaphorical code-switching, inter-sentential, and intra-sentential code-switching. Furthermore, it reveals that several studies emphasize the impact of socio-attitudinal factors on code-switching behaviors in teachers and students. This study contributes to the understanding of code-switching by offering a thorough analysis of its categories and methodology during the last 10 years. It highlights the complexities of code-switching across linguistic and cultural contexts, and it argues for multidisciplinary approaches to investigating language usage and communication issues in multiple sociocultural settings.